Field Demonstration of Heat Technology to Mitigate Heat Sinks for Drywood Termite (Blattodea: Kalotermitidae) Management - Jia-Wei Tay; Devon James (Insects, 2021)
With heat treatments to control drywood termites (Blattodea: Kalotermitidae), the presence of heat sinks causes heat to be distributed unevenly throughout the treatment areas. Drywood termites may move to galleries in heat sink areas to avoid exposure to lethal temperatures. Our studies were conducted in Crytotermes brevis-infested condominiums in Honolulu, Hawaii to reflect real-world condominium scenarios; either a standard heat treatment performed by a heat remediation company, or an improved heat treatment was used. For improved treatments, heated air was directed into the toe-kick voids of C. brevis infested cabinets to reduce heat sink effects and increase heat penetration into these difficult-to-heat areas. Eight thermistor sensors placed inside the toe-kick voids, treatment zone, embedded inside cabinets’ sidewalls, and in a wooden cube recorded target temperatures of above 46 °C or 50 °C for 120 min. Pre-treatment and follow-up inspections were performed at 6 months posttreatment to monitor termite inactivity using visual observations and by recording the numbers of spiked peaks on a microwave technology termite detection device (Termatrac). In improved treatment condominiums, significantly higher numbers of spiked peaks were recorded at pre-treatment as compared to 6 months posttreatment. Efficacious heat treatment protocols using the improved methods are proposed.